Demand for environmental quality the case of eco-friendly technologies in crop production - Divya K (Department of Agricultural Economics, College of Horticulture, 2007)
The study entitled “Demand for Environmental Quality – The case of eco-friendly technologies in crop production” was conducted in Thrissur district of Kerala state, on two major food crops (rice and banana). The main objectives were analysing the market structure of organic inputs in agriculture and identifying the factors influencing the adoption of ecofriendly technologies. The study was undertaken during March to July 2007.